Prospects for tax reform in China following the 18th CPC National Congress - Zhiyong Yang (China Finance and Economic Review, 2015)
After the 18th National Congress, the Chinese government should speed up tax reform and tax reduction. Tax structure should switch to direct tax. Consumption tax reform of lower tax burden could start within a short time. Replacing business tax by value-added tax should be quickly completed. Personal income tax reform should move toward comprehension. Uneven resource distribution should be taken into consideration in resource tax reform. Property tax should be included in the local financing service, and tax rate must be lower than other nation imposing private property rights. Looking at the long term, export should reinstate to zero export rate regime.
Keywords: 330; China's tax reform; Fiscal policy; Chinese economy